Brain Imaging and Behavior - Saykin, Andrew J.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Brain Imaging and Behavior is a bi-monthly, peer-reviewed journal that publishes innovative, clinically-relevant research using neuroimaging approaches to enhance knowledge regarding mechanisms, diagnosis, treatment, and prevention of disorders of higher brain function including cognition, affect, and motivation. Priority is given to innovative reports describing applications of advanced magnetic resonance imaging and positron emission tomography. Novel studies employing other neuroimaging methods may be considered on a case by case basis, especially if coupled with MRI or PET. Examples of particularly relevant types of studies include the use of brain imaging for identification of at-risk populations, diagnosis and treatment planning, and for monitoring the effects of behavioral, pharmacological, and neurosurgical interventions. Novel research on individual differences in representation of normal functions will also be considered in the context of large well-powered studies. Studies bridging the higher cognitive and molecular levels of analysis are particularly welcome including, for example, research relating genetic polymorphisms and other biomarkers to brain structure, function or treatment-induced changes. Translational imaging studies in model systems will also be considered if directly relevant to human disorders and treatment. These examples are meant to be illustrative and not exclusive. The research published in this journal is expected to be of broad interest to researchers and clinicians in fields addressing brain-behavior relationships (e.g., neuropsychology, psychiatry, neurology, neurosurgery, radiology, rehabilitation, and cognitive neuroscience). The journal publishes original research, brief reports, systematic reviews, and letters to the editor.
Keywords: Neurosciences; Neuroradiology; Psychiatry; Neuropsychology; Neurosciences; Neuroradiology; Neuropsychology; Psychiatry